2016
DOI: 10.1002/lt.24500
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of early relaparotomy following living donor liver transplantation

Abstract: We retrospectively analyzed the causes, risk factors, and impact of early relaparotomy after adult-to-adult living donor liver transplantation (LDLT) on the posttransplant outcome. Adult recipients who underwent initial LDLT at our institution between August 1997 and August 2015 (n = 196) were included. Any patients who required early retransplantation were excluded. Early relaparotomy was defined as surgical treatment within 30 days after LDLT. Relaparotomy was performed 66 times in 52 recipients (a maximum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 18 publications
(47 reference statements)
2
41
1
Order By: Relevance
“…Further analyses with a larger number of patients in a well‐designed multicenter study are needed to clarify the impact of early relaparotomy on outcomes. In addition, we defined early relaparotomy as a surgical intervention performed within 3 months after LDLT or during the initial hospital stay after LDLT described in recent studies . In some patients, the initial hospital stay of pediatric LDLT recipients lasted several months, and bacterial infections have been reported to be predominant during the first 2 months after transplantation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analyses with a larger number of patients in a well‐designed multicenter study are needed to clarify the impact of early relaparotomy on outcomes. In addition, we defined early relaparotomy as a surgical intervention performed within 3 months after LDLT or during the initial hospital stay after LDLT described in recent studies . In some patients, the initial hospital stay of pediatric LDLT recipients lasted several months, and bacterial infections have been reported to be predominant during the first 2 months after transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…Early relaparotomy of a recipient after adult living donor liver transplantation (LDLT) is significantly associated with a poor prognosis . Some studies have reported that the survival rate among those who require early relaparotomy is approximately 60%‐70%, which is lower than that of those who do not require early relaparotomy .…”
mentioning
confidence: 99%
“…From January 2008 to June 2016, a total of 150 adult patients underwent LDLT at Nagasaki University Hospital. Technical details about the surgical procedure applied for LDLT have already been described elsewhere . Twelve patients were excluded due to their imaging data being unavailable.…”
Section: Methodsmentioning
confidence: 99%
“…A tube jejunostomy was placed at the time of LT, and 24 hours postoperatively, enteral nutrition with Elental (Ajinomoto Pharmaceutical Ltd, Tokyo, Japan) was instituted as also previously described . The calories load was 1 kcal/mL, and the initial infusion rate was 10 mL/h.…”
Section: Methodsmentioning
confidence: 99%
“…If the patient had pretransplant infection within 2 weeks prior to LDLT, their antimicrobial therapy was continued perioperatively. Prophylactic valganciclovir (10 mg/kg/day) was given for 14 days when anticytomegalovirus immunoglobulin G was positive in the donor and negative in the recipient; trimethoprim–sulfamethoxazole (1 g daily) was given for Pneumocystis jirovecii pneumonia prophylaxis for 3 months . Early nutritional therapy was given to all recipients by tube jejunostomy or nasojejunal feeding tube from the day of LDLT to the day when the recipient could eat sufficiently.…”
Section: Methodsmentioning
confidence: 99%